Practices and Challenges of Veterinary Paraprofessionals in Regards to Antimicrobial Use and Resistance in Animals in Dar Es Salaam, Tanzania - Gasto Frumence; Leonard E. G. Mboera; Calvin Sindato; Anna Durrance-Bagale; Anne-Sophie Jung; Stephen E. Mshana; Taane G. Clark; Helena Legido-Quigley; Mecky I. Matee (MDPI AG, 2021)
We conducted a qualitative study to explore the practices and challenges of veterinary paraprofessionals (paravets) on antimicrobial use and resistance in domestic animals. Methods: This was a qualitative study, which involved semi-structured interviews with paravets from the Ilala, Ubungo, Kigamboni, Kinondoni, and Temeke districts in Dar es Salaam, Tanzania. Results: A total of 40 paravets participated in this study. The majority (72.5%) admitted to having not undergone any formal training on antimicrobial use and/or resistance. Paravets face several challenges, including poor working conditions and having no access to laboratory services to advise on antimicrobial choice and selection. They also face challenges from livestock farmers such as the inability to afford the recommended medicines, the self-prescription of antimicrobials, and poor record keeping. The presence of sub-standard medicine and the lack of guidelines on the appropriate disposal of medicines were also identified as affecting their services. Conclusion: Paravets should be trained in the judicious use of antimicrobials, and the same training should be used to refresh their knowledge on the diagnosis and prevention of infections. The Veterinary Council of Tanzania and other regulatory agencies should assist in addressing the challenges facing paravets that are related to animal health services and the quality of medicines.